Enhancing Punishment or Repairing Harms? Perceptions of Sentencing Hate Crimes Amongst Members of a Commonly Targeted Victim Group - Walters, Mark Austin (The British journal of criminology, 2021)
This article investigates the attitudes and emotional reactions of LGBT+ people to enhanced sentencing (ES) and restorative justice (RJ) interventions for hate crime. When forced to choose between interventions, our survey (N = 589) found a preference for the use of RJ over ES, which was perceived to be better at reducing reoffending and supporting victims. Nevertheless, the study found greater average levels of support for the use of ES for hate crime, which was predicted by previous experiences of hate crime, perceptions of threat and feelings of anger. An additional experiment (N = 120) revealed RJ, in response to a hate crime, elicited less anger and sadness and higher levels of satisfaction compared with an ES intervention.